Graph-Based Symbolic Technique and Its Application in the Frequency Response Bound Analysis of Analog Integrated Circuits - E. Tlelo-Cuautle; S. Rodriguez-Chavez; A. A. Palma-Rodriguez (The Scientific World Journal)
A new graph-based symbolic technique (GBST) for deriving exact analytical expressions like the transfer function H(s) of an analog integrated circuit (IC), is introduced herein. The derived H(s) of a given analog IC is used to compute the frequency response bounds (maximum and minimum) associated to the magnitude and phase of H(s), subject to some ranges of process variational parameters, and by performing nonlinear constrained optimization. Our simulations demonstrate the usefulness of the new GBST for deriving the exact symbolic expression for H(s), and the last section highlights the good agreement between the frequency response bounds computed by our variational analysis approach versus traditional Monte Carlo simulations. As a conclusion, performing variational analysis using our proposed GBST for computing the frequency response bounds of analog ICs, shows a gain in computing time of 100x for a differential circuit topology and 50x for a 3-stage amplifier, compared to traditional Monte Carlo simulations.